Evaluation of Amino Acid Needs of Large White Male Turkeys on an Age-Adjusted Basis - Waldroup, P.W.; England, J.A. (International Journal of Poultry Science, 2002)
The increased growth rate of Large White turkeys has prompted producers to change feeds at more frequent intervals than previously. However, nutrient recommendations by established agencies such as the National Research Council (1994) have not adjusted to this change. Using regression analysis of published amino acid recommendations, modified amino acid recommendations were calculated for feeding on three week intervals. Male Large White turkeys were fed diets formulated to provide from 90 to 115% of the modified recommendations from day-old to 18 weeks of age; samples of the birds were processed to determine carcass characteristics. Based upon the results of the present study, the amino acid recommendations derived from regression analysis of NRC recommendations appear to be a good basis for use when changing diets at intervals of 3 week for male Large White turkeys. To insure maximum breast meat yield, these should be increased by approximately 5%.